Improved reliability of wind turbine towers with active tuned mass dampers (ATMDs). (14th April 2018) - Fitzgerald, Breiffni; Sarkar, Saptarshi; Staino, Andrea
Abstract: Modern multi-megawatt wind turbines are composed of slender, flexible, and lightly damped blades and towers. These components exhibit high susceptibility to wind-induced vibrations. As the size, flexibility and cost of the towers have increased in recent years, the need to protect these structures against damage induced by turbulent aerodynamic loading has become apparent. This paper combines structural dynamic models and probabilistic assessment tools to demonstrate improvements in structural reliability when modern wind turbine towers are equipped with active tuned mass dampers (ATMDs). This study proposes a multi-modal wind turbine model for wind turbine control design and analysis. This study incorporates an ATMD into the tower of this model. The model is subjected to stochastically generated wind loads of varying speeds to develop wind-induced probabilistic demand models for towers of modern multi-megawatt wind turbines under structural uncertainty. Numerical simulations have been carried out to ascertain the effectiveness of the active control system to improve the structural performance of the wind turbine and its reliability. The study constructs fragility curves, which illustrate reductions in the vulnerability of towers to wind loading owing to the inclusion of the damper. Results show that the active controller is successful in increasing the reliability of the tower responses. According to the analysis carried out in this paper, a strong reduction of the probability of exceeding a given displacement at the rated wind speed has been observed. Highlights: Improvements in structural reliability when wind turbine towers equipped with ATMD. Proposed controller is capable of remarkably improving the response of tower. Fragility curves illustrate reductions in the vulnerability of tower due to ATMD. Active controller is successful in increasing the reliability of the tower response. Large reduction in the probability of exceeding a given displacement at rated speed.